2015
DOI: 10.1027/1864-9335/a000241
|View full text |Cite
|
Sign up to set email alerts
|

Apple or Chocolate – Intentional and Social-Reactive Processes in Eating Behavior Among Adolescents

Abstract: Abstract. Two studies examined the main assumption of the Prototype/Willingness Model for eating behavior. Accordingly, health-behavior in adolescents results from intentional and social-reactive processes, namely behavioral intentions and behavioral willingness. The hypothesis was that willingness explains eating behavior over and above intentions with respect to eating behavior in general and in the peer context. This was tested in a cross-sectional (N = 286) and a longitudinal (N = 335) study. Intentions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Finally, the entire PWM with its two pathways was tested using structural equation modeling (SEM) and found to explain 21.2% to 51.6% of the behavior variance (Dohnke, Steinhilber, & Fuchs, 2015; Steinhilber & Dohnke, 2014). In sum, these studies demonstrate the PWM with its social–cognitive factors to be relevant for the explanation of eating behavior in different cultures such as in the Netherlands (Gerrits et al, 2009), in Germany (Steinhilber et al, 2013; Fuchs et al, in press; Dohnke et al, 2015; Steinhilber & Dohnke, 2014), in the United States, in Hungary (Gerrits et al, 2010), in Japan (Ohtomo et al, 2011), and in Turkey (Steinhilber & Dohnke, 2014). To our knowledge, however, only one cross-cultural study tested differences between cultural groups: It revealed comparable prediction patterns of the social–cognitive factors among samples of adolescent nonmigrants in Turkey and in Germany (Steinhilber & Dohnke, 2014).…”
Section: The Prototype-willingness Modelmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, the entire PWM with its two pathways was tested using structural equation modeling (SEM) and found to explain 21.2% to 51.6% of the behavior variance (Dohnke, Steinhilber, & Fuchs, 2015; Steinhilber & Dohnke, 2014). In sum, these studies demonstrate the PWM with its social–cognitive factors to be relevant for the explanation of eating behavior in different cultures such as in the Netherlands (Gerrits et al, 2009), in Germany (Steinhilber et al, 2013; Fuchs et al, in press; Dohnke et al, 2015; Steinhilber & Dohnke, 2014), in the United States, in Hungary (Gerrits et al, 2010), in Japan (Ohtomo et al, 2011), and in Turkey (Steinhilber & Dohnke, 2014). To our knowledge, however, only one cross-cultural study tested differences between cultural groups: It revealed comparable prediction patterns of the social–cognitive factors among samples of adolescent nonmigrants in Turkey and in Germany (Steinhilber & Dohnke, 2014).…”
Section: The Prototype-willingness Modelmentioning
confidence: 87%
“…In addition, the perception of the healthy eater was found to be associated with the consumption of fruit and vegetables (Gerrits et al, 2010) and general eating behavior (Steinhilber et al, 2013). Furthermore, willingness predicted eating behavior over and above intentions (Fuchs, Steinhilber, & Dohnke, in press) and the consumption of unhealthy foods 3 (Ohtomo, Hirose, & Midden, 2011). Finally, the entire PWM with its two pathways was tested using structural equation modeling (SEM) and found to explain 21.2% to 51.6% of the behavior variance (Dohnke, Steinhilber, & Fuchs, 2015; Steinhilber & Dohnke, 2014).…”
Section: The Prototype-willingness Modelmentioning
confidence: 99%
“…It was measured by behavioural observation in the peer context at T2 and T3 and a 24-h recall at T3, baseline values at T1 (Table III). The observation took place in two situations in which ready-to-eat food was offered, either fruit or sweets (for details see Dohnke et al , 2018; Fuchs et al , 2015). The amounts taken were recorded inconspicuously and aggregated across fruit and sweets by taking the mean.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the study groups differed in age and order of food offered, so that any effects on the outcomes were statistically controlled for. Third, behavioural effects were mixed: they were not consistent across the two follow-up times, but across two indicators (T3) which reflect different facets of food consumption and were assessed by different methods: in the peer context by observation and in general by self-report (Dohnke et al , 2015; Fuchs et al , 2015). The results may nevertheless be considered promising, as the present study is one of few that tested effects of a prototype-targeting intervention on behaviour (Teunissen et al , 2012), not only on willingness (Blanton et al , 2001) or other cognitions.…”
Section: Discussionmentioning
confidence: 99%
“…They also completed a measure of self-reported body composition avoidance (8 items, α = .899; range = 1-6; Howell & Shepperd, 2016; e.g., "I would rather not know my body composition."). The survey then assessed their healthy eating intentions (i.e., intentions to eat fruit, green salad, and nonfried vegetables; three items; α = .723; Fuchs et al, 2015) and their unhealthy eating intentions (i.e., intentions to eat sweets, fast food, salty snacks, and sugary drinks; four items; α = .640; Fuchs et al, 2015) in the next month on a scale from 1 (=not at all) to 6 (=3 or more times per day). Exercise intentions were measured through two items assessing their intentions and likelihood for engaging in physical activity in the next month (r = .817).…”
Section: Timementioning
confidence: 99%